A grocery list learning and memory screening test: Initial performance data stratified by age and IQ. Issue 4 (4th July 2023) - Hart, Lance Roderic
Abstract: Patients frequently verbalize memory complaints that require evaluation. A brief objective screening test of short-term aka episodic memory would be useful. Assessment of verbal episodic memory is a central factor in neurocognitive status, frequently evaluated with list learning and memory tests. Currently, normed list learning tests of verbal episodic memory are mostly high demand, long, and composed of unrelated items and thus can be onerous and disinteresting for certain populations, such as those who are cognitively limited, elderly, or poorly motivated. Presented here are initial performance data for a brief, low demand, readily accepted nine-item grocery list test, derived from the Dementia Assessment Battery, including three learning trials and one delayed recall trial. With this data set, the test can thus be useful in a wide range of assessment circumstances including screening, brief evaluations, mental status evaluations, and bedside deployment.